Early Exposure to a Clinical Oncology Course During the Preclinical Second Year of Medical School. (April 2015) - Granek, Leeat; Lazarev, Irena; Birenstock-Cohen, Shira; Geffen, David B.; Riesenberg, Klaris; Ariad, Samuel
Abstract : Problem: Although only some medical students pursue a career in oncology, all should have a basic understanding of the issues surrounding cancer and its treatment. The authors designed and implemented a one-week introductory clinical oncology course for second-year medical students at Ben Gurion University of the Negev. The course presents a holistic approach to caring for patients with cancer that goes beyond the biological aspects of the disease. Approach: In 2013, the authors interviewed four former students and surveyed all current students before and after they completed the course to evaluate its reception and effectiveness. Outcomes: Of the 86 students in the course, 77 (90%) completed both the pre- and postcourse surveys. After taking the course, more students reported being concerned about ethical issues, being emotionally stirred by the course, being comfortable speaking with a cancer patient about death and dying, and being comfortable with the fact that the course dealt with issues of death and loss and with "how to live with cancer." In addition, more students reported a fear of causing a cancer patient suffering because of a treatment yet viewed cancer optimistically. Finally, more students considered specializing in oncology. Next Steps: That students reported increased empathy toward cancer patients despite increased trepidation about causing them suffering is promising. Such courses may be one way to counteract the decrease in empathy among students as they progress through medical school. As such, medical schools might consider including this type of curriculum in their preclinical oncology studies.